The Role of Islamic Religious Education in Forming Anti-Online Gambling Awareness Among Youth in Kalilangkap Village, Central Java Province - Siti Aisah; Leli Fertiliana Dea; Lutfi Fadilah (Journal of Research in Islamic Education, 2026)
This study aims to analyze the role of Islamic Religious Education in shaping anti-online gambling awareness among adolescents in Kalilangkap Village, Central Java Province, and to identify its supporting and inhibiting factors. The development of digital technology increases adolescents' exposure to various risky behaviors, including online gambling, which has the potential to affect self-control and character formation, thereby necessitating the strengthening of the role of value-based education. Using a qualitative approach, data were collected through observation techniques, documentation studies, and in-depth interviews with adolescents, parents, and religious and community leaders. The results indicate that Islamic Religious Education plays a significant role through the internalization of faith values, the strengthening of moral conduct, and the development of self-control, which encourages an attitude of rejecting risky behavior in the digital space. The effectiveness of this role is strengthened by the collaboration of the family and a conducive social environment. The main supporting factors include the role modeling provided by parents and religious figures, while the inhibiting factors include limited parental guidance, peer influence, and the absence of specific educational programs addressing the challenges of the digital space.